Sosiologi Pendidikan Dalam Pembentukan Karakter Peserta Didik Di Sekolah - Khaerul Dionprawitno; Nur Khasanah (Yayasan Al-Afif, 2025)
this article aims to explain the role of sociology in building students’ character. sociology is a social science that studies social facts, social norms, and various forms of social deviation, which are important factors in the process of character formation among students. this study uses a qualitative approach with a library research method. the data sources are obtained from relevant literature, academic journals, and books related to sociology of education. all collected data are analyzed descriptively to draw comprehensive conclusions. the results of this study indicate that sociology of education, as a branch of sociology, plays a significant role in shaping students’ character in schools, particularly through the understanding of values, norms, and social interactions within the educational process.